Serum amino acid profile in patients with Parkinson’s disease - Figura, Monika; Kuśmierska, Katarzyna; Bucior, Ewelina; Szlufik, Stanisław; Koziorowski, Dariusz; Jamrozik, Zygmunt; Janik, Piotr (PloS one, 2018)
Amino acids play numerous roles in the central nervous system, serving as neurotransmitters, neuromodulators and regulators of energy metabolism. The free amino acid profile in serum of Parkinson's disease (PD) patients may be influenced by neurodegeneration, mitochondrial dysfunction, malabsorption in the gastroenteric tract and received treatment. The aim of our study was the evaluation of the profile of amino acid concentrations against disease progression. We assessed the amino acid profile in the serum of 73 patients divided into groups with early PD, late PD with dyskinesia and late PD without dyskinesia. Serum amino acid analysis was performed by high-pressure liquid chromatography with fluorescence detection. We observed some significant differences amongst the groups with respect to concentrations of alanine, arginine, phenylalanine and threonine, although no significant differences were observed between patients with advanced PD with and without dyskinesia. We conclude that this specific amino acid profile could serve as biochemical marker of PD progression.